2012
DOI: 10.1016/j.neuroscience.2012.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of progesterone receptor suppresses carotid body responses to hypoxia and nicotine in rat pups

Abstract: We tested the hypothesis that antagonism of progesterone receptor (PR) in newborn rats alters carotid body and respiratory responses to hypoxia and nicotinic receptor agonists. Rats were treated with the PR antagonist mifepristone (daily oral gavage 40 μg/g/d) or vehicle between postnatal days 3 and 15. In 11-14-day-old rats, we used in vitro carotid body/carotid sinus nerve preparation and whole body plethysmography to assess the carotid body and ventilatory responses to hypoxia (65 mmHg in vitro, 10% O2 in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…In this model of vagotomized and chemodenervated cats, the effects of progesterone on respiratory activity is primarily mediated by the hypothalamus [5], but the injection of progesterone in the NTS also increases respiratory activity [6]. Chronic treatment with mifepristone in newborn rats abolished carotid body responses to hypoxia [12], while progesterone treatment in adult cats enhances the carotid body response to hypoxia [7]. Progesterone combined with estradiol in rats enhances ventilation by decreasing the synthesis of the inhibitory neurotransmitter dopamine in the carotid body [32], which is consistent with the effect of the progesterone receptor on the expression of tyrosine hydroxylase [33], the rate-limiting enzyme in dopamine synthesis.…”
Section: Discussionmentioning
confidence: 93%
“…In this model of vagotomized and chemodenervated cats, the effects of progesterone on respiratory activity is primarily mediated by the hypothalamus [5], but the injection of progesterone in the NTS also increases respiratory activity [6]. Chronic treatment with mifepristone in newborn rats abolished carotid body responses to hypoxia [12], while progesterone treatment in adult cats enhances the carotid body response to hypoxia [7]. Progesterone combined with estradiol in rats enhances ventilation by decreasing the synthesis of the inhibitory neurotransmitter dopamine in the carotid body [32], which is consistent with the effect of the progesterone receptor on the expression of tyrosine hydroxylase [33], the rate-limiting enzyme in dopamine synthesis.…”
Section: Discussionmentioning
confidence: 93%
“…We previously reported that mifepristone administration reduces the carotid sinus nerve response to hypoxia (Joseph et al . ), which is thought to play an important role in the early phase of the HVR. Accordingly, we focused the present study on the steady‐state phase of the HVR, mostly characterized in neonates by central respiratory inhibition (Bissonnette, ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously, in newborn rats, that daily administration of mifepristone, a non‐specific progesterone receptor antagonist, dramatically decreases the carotid sinus nerve response to hypoxia (Joseph et al . ), suggesting a key contribution of endogenous progesterone for adequate development of the respiratory response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…31.1 ). We used the standard in vitro recording of the CSN activity, as previously described (Joseph et al 2012 ). In brief, the preparation was transferred to a recording chamber, thermostated at 36 °C (TC2Bip temperature controller; Cell Micro-Controls; Norfolk, VA, USA), and superfused at a fl ow rate of 6 mL/min with Tyrode solution bubbled with 5 % CO 2 balance in O 2 ; pH 7.4.…”
Section: Ex Vivo Electrophysiological Recording Of the Carotid Sinus mentioning
confidence: 99%